Immunochemical properties of the N-terminal helix of myotoxin II, a lysine-49 phospholipase A2 from Bothrops asper snake venom - Angulo Ugalde, Yamileth (2001)
Myotoxic class II phospholipases A2 from snake venoms can be divided into Asp49 and Lys49 types. The latter, including Bothrops asper myotoxin II, exert membrane damage despite lacking catalytic activity. A heparin-binding, hydrophobic/ cationic region, near the C-terminus of myotoxin II (115±129) has been shown to be relevant in its membrane-damaging actions. However, some observations suggest also a potential participation of its N-terminal region. An immunochemical approach was utilized to examine the properties and possible role in toxicity of the N-terminal helix of myotoxin II. Rabbit antibodies raised to a synthetic peptide comprising residues 1±15 recognized the native protein. These antibodies were utilized to compare the antigenic characteristics of the N-terminal helix of several myotoxic phospholipases A2, showing generally stronger binding to Lys49 myotoxins, in comparison to Asp49 counterparts. However, three Lys49 myotoxins (Cerrophidion godmani myotoxin II, Atropoides nummifer myotoxin II, and Trimeresurus ¯avoviridis basic protein I) were not recognized by the antibodies, revealing a signi®cant antigenic variability of the N-terminal region within this group of toxins. In neutralization experiments, pre-incubation of myotoxin II with af®nity-puri®ed antibodies to the N-terminal helix did not inhibit its myotoxic activity in mice, nor its cytotoxic effect upon cultured muscle cells. These ®ndings argue against a critical role of the N-terminal region of this protein in toxicity. Thus, the precise role of the N-terminal helix of myotoxin II and related Lys49 phospholipases A2, regarding their toxic mechanisms, remains controversial, and requires further experimental study to be clari®ed.